Battle of the Brand: Independent “American” Universities Abroad - Long, Kyle A. (International Higher Education, 2018)
Over the past quarter century, dozens of entrepreneurs, academics, clerics, and politicians around the world have established private colleges that brandish the American name. This surge of activity has irritated the historic standard-bearers of American higher education overseas, who worry that bad faith imposters will sully their hard-earned individual and collective reputations. This article describes the challenges posed by coattail riders and identifies other common problems among independent American universities abroad.